(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cervical cancer remains a critical public health concern worldwide. Beyond its physical burden, the disease imposes significant psychological challenges that can influence patient outcomes and quality of life. This review examines prevalent psychological disturbances such as depression, anxiety, body image alterations, social withdrawal, and sexual identity disruption among affected women. It further evaluates psychosocial interventions designed to support mental well-being.